A note on solutions of wave, Laplace’s and heat equations with convolution terms by using a double Laplace transform - Eltayeb, Hassan; Kilicman, Adem (Elsevier, 2008)

(untitled)
In this study we consider general linear second-order partial differential equations and we solve three fundamental equations by replacing the non-homogeneous terms with double convolution functions and data by a single convolution